Potret Jakarta melalui Foto Dokumenter sebagai Media Komunikasi Sosial - Candrastuti, Ratih; Novianti, Erlina; Kantina, Sri (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aims to empower the community, particularly the photography community, in utilizing documentary photography as a medium of social communication in Jakarta. Cultural diversity, history, and modernity are important objects of visual documentation for urban communities. The methods used include literature studies, field observations, photography training, photography practice at a number of iconic locations, and publication of the results through social media. This activity not only improves technical skills but also the ability to interpret cultural symbols and messages in photographs. The program results in enhanced visual literacy, the availability of cultural promotion content for Jakarta, and contributions to strengthening the creative economy. This initiative is crucial for cultural preservation, public information dissemination, and increasing community participation in promoting Jakarta's urban identity in the digital age.